"THE IMPACT OF ENVIRONMENTAL POLLUTION ON THE VARIABILITY OF FRUIT GARDENS AND SOILKOMOMOKOMPLEXES (FERGANA-MARGILAN - QUVASOY INDUSTRIAL NODE)” - Xalilovich, Ganiev Komolidin; Mamatyusufo’g’li, Mirzaliyev Abdujabbor; Abdulazizovna, Xalilova Barno; Maxammadzikirovna, Gafurova Ominaxon; Tursunaliyevna, Turkistonova Maftuna (The journal of contemporary issues in business and government, 2021)
To date , the amount of industrial, household waste and chemical substances from the end of industrial enterprises of the Republic about 2.5 million tons of pollutants to the atmosphere close to 2000, about 170 million cubic meters of contaminants to the water basins and about 50 chemicals to the soil and about 150 pesticides have reached 289 million tons.